The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/mrm.28188
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 1H‐MRS for detection of 13C‐labeled glucose metabolism in the human brain at 3T

Abstract: Purpose: In 2004, Boumezbeur et al proposed a simple yet powerful approach to detect the metabolism of 13 C-enriched substrates in the brain. Their approach consisted of dynamic 1 H-MRS, without a 13 C radiofrequency (RF) channel, and its successful application was demonstrated in monkeys. Since then, this promising method has yet to be applied rigorously in humans. In this study, we revisit the use of dynamic 1 H-MRS to measure the metabolism of 13 C-enriched substrates and demonstrate its application in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…27 Other studies that reported fractional enrichments used infusion of [1- 13 C]-glucose. These studies reported maximal enrichment of 15 % to 30 % 26,[31][32][33][34][35] . The value measured in this study is in a similar range.…”
Section: Fractional Enrichments Of Glutamate and Glutaminementioning
confidence: 96%
“…27 Other studies that reported fractional enrichments used infusion of [1- 13 C]-glucose. These studies reported maximal enrichment of 15 % to 30 % 26,[31][32][33][34][35] . The value measured in this study is in a similar range.…”
Section: Fractional Enrichments Of Glutamate and Glutaminementioning
confidence: 96%
“…This approach had the advantage that it enabled quantification of the metabolic rate of LDH activity. In the future, we hope to extend our approach to enable similar quantitative metabolic flux measures in hESC-derived COs using indirect 13 C-or 2 Hlabelled glucose administration, as demonstrated previously in in vivo magnetic resonance spectroscopy (MRS) studies [14][15][16][17] . Lastly, van der Kemp et al 18 reported a comparison between HR-MAS NMR spectroscopy of intact colorectal cancer organoids, and solution NMR spectroscopy of polar extracts.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, relative to consecutive SV-MRS measurements in two VOIs, HD-SPECIAL reduces the total scan time twofold with minimal SNR loss and with minimal penalty in terms of spectral quality. In the case of dynamic measurement of metabolites with multiple VOIs, such as 13 C labeling studies 39 or functional MRS studies, 40 simultaneous measurement from two regions may be scientifically preferable, increasing the available temporal resolution by a factor of two.…”
Section: Discussionmentioning
confidence: 99%